2001
DOI: 10.1046/j.1523-536x.2001.00084.x
|View full text |Cite
|
Sign up to set email alerts
|

Immersion in Water in the First Stage of Labor: A Randomized Controlled Trial

Abstract: Bathing in labor confers no clear benefits for the laboring woman but may contribute to adverse effects in the neonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
146
5
14

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(167 citation statements)
references
References 26 publications
(32 reference statements)
2
146
5
14
Order By: Relevance
“…The positive physiological effects of hydrotherapy can facilitate the neurohormonal interactions of labour, reducing pain, and potentially facilitates the progress of labour (11,12). Water immersion may be associated with improved uterine perfusion, less painful contractions and a shorter labour with fewer interventions (13)(14)(15) sion shortens the process of labour (1,15), however some others found no significant difference for the duration of the 1st stages of labour (13,(16)(17)(18)(19)(20). The present study also demonstrates that the 1st stage of labour is not shortened by immersion in water in either primigravidas or multigravidas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive physiological effects of hydrotherapy can facilitate the neurohormonal interactions of labour, reducing pain, and potentially facilitates the progress of labour (11,12). Water immersion may be associated with improved uterine perfusion, less painful contractions and a shorter labour with fewer interventions (13)(14)(15) sion shortens the process of labour (1,15), however some others found no significant difference for the duration of the 1st stages of labour (13,(16)(17)(18)(19)(20). The present study also demonstrates that the 1st stage of labour is not shortened by immersion in water in either primigravidas or multigravidas.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also demonstrates that the 1st stage of labour is not shortened by immersion in water in either primigravidas or multigravidas. Cammu et al, Eckert et al, Rush et al and Woodward et al provided data on analgesia and anesthesia use in their studies and found that there was a significant reduction in the incidence of analgesia and anesthesia use among women placed in water during the first stage of labour (16,17,19,20). In the present study, we have shown that VAS scores indicating the pain felt by the women were lowest among women having water birth, even lower than the women labouring with epidural analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Statistically, water birth leads to increased relaxation and maternal satisfaction, decreased perineal trauma, decreased pain and use of pharmaceuticals, and decreased labor time (Benfield, Herman, Katz, Wilsonv, & Davis, 2001;Cluett, Pickering, Getliffe, & Saunders, 2004;Eckert, Turnbull, & MacLennan, 2001;Mackey, 2001;Rush et al, 1996;Thöni, Mussner, & Ploner, 2010).…”
Section: American Academy Of Pediatrics' Committee Commentarymentioning
confidence: 99%
“…Individual case reports and case series have noted complications for the mother and the neonate [17][18][19][20][21][22][23][24][25] that highlight potential risks from immersion during labor and delivery. Because the denominators are not uniformly reported, the exact incidence of complications is difficult to assess.…”
Section: Reported Complications From Immersion During Labor and Deliverymentioning
confidence: 99%